Validating subject‐specific RF and thermal simulations in the calf muscle using MR‐based temperature measurements - Simonis, F.F.J.; Raaijmakers, A.J.E.; Lagendijk, J.J.W.; van den Berg, C.A.T. (Magnetic resonance in medicine, 2017)
Purpose Ongoing discussions occur to translate the safety restrictions on MR scanners from specific absorption rate (SAR) to thermal dose. Therefore, this research focuses on the accuracy of thermal simulations in human subjects during an MR exam, which is fundamental information in that debate. Methods Radiofrequency (RF) heating experiments were performed on the calves of 13 healthy subjects using a dedicated transmit‐receive coil while monitoring the temperature with proton resonance frequency shift (PRFS) thermometry. Subject‐specific models and one generic model were used for electromagnetic and thermal simulations using Pennes' bioheat equation, with the blood equilibration constant equaling zero. The simulations were subsequently compared with the experimental results. Results The mean B1+ equaled 15 µT in the center slice of all volunteers, and 95% of the voxels had errors smaller than 2.8 µT between the simulation and measurement. The intersubject variation in RF power to achieve the required B1+ was 11%. The resulting intersubject variation in median temperature rise was 14%. Thermal simulations underestimated the median temperature increase on average, with 34% in subject‐specific models and 28% in the generic model. Conclusions Although thermal measures are directly coupled to tissue damage and therefore suitable for RF safety assessment, insecurities in the applied thermal modeling limit their estimation accuracy. Magn Reson Med 77:1691–1700, 2017. © 2016 International Society for Magnetic Resonance in Medicine